Decolonizing conservation, a global conversation: views from Turtle Island, Tanzania, and Thailand - Bright, Saw John; Carroll, Clint; Goldman, Mara J.; Low, Margaret; Loure, Edward; Roth, Robin (Frontiers in Human Dynamics, 2025)
What does it mean to decolonize conservation? This question was posed to a group of scholars and activists working in different places around the world – the US, Canada, Tanzania, and Thailand. This article is an edited transcript of the conversation that ensued. The goal of this paper is to keep that conversation alive and continue to add nuance and curiosity to the question as it unfolds in similar and different places around the world. A key feature of continuing important dialogues such as this one, is to resist the temptation to offer definitive definitions of what it would take to decolonize conservation but rather seek out greater understanding of what it might look like in a variety of places. Amongst deepening calls for greater Indigenous inclusion as states seek to implement the Global Biodiversity Framework, it is vital we keep questions of what constitutes decolonized conservation top of mind.